Site-specific control of silica mineralization on DNA using a designed peptide. Issue 21 (22nd December 2015) - Ozaki, Makoto; Nagai, Kazuma; Nishiyama, Hiroto; Tsuruoka, Takaaki; Fujii, Satoshi; Endoh, Tamaki; Imai, Takahito; Tomizaki, Kin-ya; Usui, Kenji
Abstract : We developed a site-specific method for precipitating inorganic compounds using organic compounds, DNA, and designed peptides with peptide nucleic acids (PNAs). Abstract : We developed a site-specific method for precipitating inorganic compounds using organic compounds, DNA, and designed peptides with peptide nucleic acids (PNAs). Such a system for site-specific precipitation represents a powerful tool for use in nanobiochemistry and materials chemistry.